Joint kinematics during indoor bend sprinting - White, J.; Irwin, G.; Exell, T.; Wilson, C.; Hamill, J.; Wyatt, H.; von Lieres und Wilkau, H.; Weir, G. (ISBS Proceedings Archive (Michigan), 2022)
The aim of this study was to identify the effect of radius on lower extremity joint kinematics during indoor bend sprinting. Kinematic data (250 Hz) were collected from eight well-trained sprinters during two ~80 m sprints in banked lanes 2 and lane 4. One-dimensional Statistical Parametric Mapping was used to analyse lower extremity joint kinematics during the stance phase. Similar to previous bend sprinting research, this study found the left limb appears to adopt an adduction and eversion strategy during left stance to control the movement demands of bend sprinting. Furthermore, significant inter-limb asymmetry occurred primarily in lane 2, highlighting that tightening the radii of the lane brought about increased inter-limb asymmetry.